Accuracy of talonavicular injection using ultrasound versus anatomical landmark: a cadaver study. (October 2020) - Jha, Aaradhana J; Viner, Gean C; McKissack, Haley; Anderson, Matthew; Prather, John; Shah, Ashish B; Caycedo, Francisco
Background: Intra-articular injections have diagnostic and therapeutic roles in foot and ankle pathologies due to complex anatomy, small size, diverse bones, and joints with proximity in this region. Conventionally, these injections are carried out using anatomical landmark technique and/or fluoroscopic guidance. The small joint space and needle size make the injection challenging. Fluoroscopy is not readily available in the clinical setting; ultrasound-guidance for injections is therefore increasingly being used. We compared the accuracy of intra-articular talonavicular injections using the anatomical landmark technique versus the ultrasound-guided method. Purpose: To determine whether ultrasound guidance yields superior results in intra-articular injections of the talonavicular joint compared to injections using palpatory method guided by anatomical landmarks. Material and Methods: The feet of 10 cadaveric specimens were held in neutral position by an assistant while a fellowship-trained foot-ankle orthopedic surgeon injected 2 cc of radiopaque dye using anatomical landmarks and palpation method in five specimens and under ultrasound guidance in the remaining five. The needles were left in situ in all specimens and their placement was confirmed fluoroscopically. Results: In all five specimens injected under ultrasound guidance, the needle was found to be in the joint, whereas all five injected by palpation only were out of the joint, with one in the naviculo-cuneiform joint, showing ultrasound guidance to significantly increase the accuracy of intra-articular injections in the talonavicular joint than palpatory method alone. Conclusion: Ultrasound-guided injections not only confirm correct needle placement, but also delineate any tendon and/or joint pathology simultaneously.